Synergy effects of hindered phenol and diphosphite antioxidants on promoting alkali resistance of quaternary ammonium functionalized poly(4-vinylbenzyl chloride-styrene) anion exchange membranes. (1st June 2021) - Peng, Xiaomeng; Yang, Yunfei; Ye, Niya; Xu, Shicheng; Zhang, Dengji; Wan, Ruiying; He, Ronghuan
Highlights: Promote alkali resistance of the membrane by doping with dual antioxidants. Efficient synergy effects of hindered phenol and diphosphite on scavenging free radicals. About 80% of the original conductivity is retained after soaked the membrane in 2 M KOH at 60 °C for 1300 h. A peak power density of 526 mW cm −2 is reached based on the proposed membrane. Abstract: The anion exchange membranes (AEMs) possessing a long-term alkaline stability is desired for use as the electrolyte in electrochemical devices. We prepared a series of AEMs with excellent stability and reasonable conductivity as well as acceptable mechanical properties by addition of antioxidants into quaternary ammonium modified poly(4-vinylbenzyl chloride-styrene). It is found that the synergy of hindered phenol and diphosphite antioxidants endowed the AEMs with superior resistance to the attack of both OH – ions and free radicals. The proposed membrane retained about 80% of the original conductivity after soaked in 2 M KOH aqueous solutions at 60 o C for 1300 h. The synergy effect of the dual antioxidants was investigated by Fenton tests and the fluorescence analysis. A peak power density of 526 mW cm −2 was achieved at 60 o C by the membrane-based single fuel cell fueling with humidified H2 and O2 without back pressure. Graphical abstract: Image, graphical abstract